PENGARUH KUALITAS LAYANAN, CITRA PERUSAHAAN, DAN PERSEPSI HARGA TERHADAP KEPUASAN KONSUMEN (Studi Kasus Pada Pengguna Jasa Servis Kendaraan Roda Dua Di Yamaha Agung Motor Semarang) - Amanda Prasetya, 09.05.51.0091 (Students Journal of Economic and Management, 2015)
This study analyzed the quality of service (X1), the image of the company (X2), and the perception of the price (X3) on consumer satisfaction (Y). The population in this study is the great customer service yamaha motor using quality of service, corporate image, and price. The samples made with the technique of